Water carrying in hills of Nepal–associations with women’s musculoskeletal disorders, uterine prolapse, and spontaneous abortions - Meierhofer, Regula; Tomberge, Vica Marie Jelena; Inauen, Jennifer; Shrestha, Akina (PLOS ONE, 2022)
More than a third of women in Nepal have to carry water from source to home to satisfy their families’ daily needs. A cross-sectional study was carried out in a hilly area in Nepal to assess water-carrying practices and their association with women’s health. Quantitative interviews were conducted with 1001 women of reproductive age and were complemented with health surveys carried out by health professionals and structured observations of water carrying. Multivariate mixed logistic regression models were used to assess the associations between water-carrying-related risk factors and health issues for women. Around 46% of women faced considerably increased to excessive physical stress due to water carrying during the dry season. Women suffered from a disproportionately high prevalence of back pain (61%), with about 18% of this pain being horrible to excruciating; pain in the knees (34%); uterine prolapse (11.3%); and at least one spontaneous abortion (9%). The risk category of water carrying was significantly associated with uterine prolapse (OR = 1.44, 95%CI = 1.12–1.85, p = 0.031) and pain in the hips (OR = 1.69, 95%CI = 1.27–2.26, p<0.001). Receiving help with water carrying during pregnancy and during the first three months after delivery was associated with reduced odds ratios for uterine prolapse (OR = 0.10, 95% CI = 0.01–0.87, p = 0.037), and strong back pain (OR = 0.32, 95% CI = 0.12–0.87, p = 0.026). Improvements to water supply infrastructure and the promotion of social support for carrying water during pregnancy and after delivery are recommended to reduce water-carrying-related health risks.